Analisis Yuridis Pemberian Ganti Kerugian Dalam Pengadaan Tanah Di Bawah 5 (Lima) Hektar (Pembangunan Instalasi Pengelolaan Air Sistem Penyediaan Air Minum (Ipa Spam) Regional Jatiluhur I) - Silvianingtias, Indah; Budisetyowati, Dwi Andayani; Atmoko*, Dwi (Universitas Syiah Kuala, 2023)
In the juridical analysis, the granting of compensation in land acquisition under 5 (five) construction of a water management installation for the Jatiluhur Regional Drinking Water Supply System (IPA SPAM). Water Management Installation for Drinking Water Supply Systems (IPA SPAM) covering an area of 32,554 m2 or (3.26 Ha) through land acquisition for development in the public interest which is now also an urgency for the government because it is considered to be able to support national welfare and development, the Government of Indonesia officially passed Perpu Number 2 of 2022 concerning Job Creation to deal with the global economic crisis, the threat of inflation, and the current multi-sector crisis that has not been able to meet legal requirements. Analysis related to whether land acquisition under 5 (five) hectares (Development for Water Management Installation for Jatiluhur I Regional Drinking Water Supply System (IPA SPAM) in Bekasi City is in accordance with Perpu No. 2 of 2022 and how are the efforts to provide compensation for land acquisition, with the general research objective is to study Land Procurement Under 5 (Five) hectares and specifically to find out the obstacles and efforts in overcoming the problem of giving compensation, the research method used in this research is normative juridical research. Furthermore, here we discuss efforts that can be made where one of the solutions is by entrusting compensation in court to people who object, while efforts can be made for communities on land assets to provide compensation by adhering to the principle of horizontal separation then, the presence of the Perpu can also be an effort to implement and resolve obstacles to land acquisition.